IMPLEMENTASI AKUNTANSI AKRESI PADA ASET BIOLOGIS DENGAN PENDEKATAN NILAI WAJAR DAN BIAYA PADA PETERNAKAN BRAWIJAYA FARM - Akbar Masnur Achmad Al -W; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2023)
Companies engaged in agriculture have their own characteristics in their business financial reporting when compared to companies engaged in sectors other than agriculture, because agricultural companies have fundamental differences in the types of assets managed. Agricultural companies manage biological assets that undergo natural biological growth or transformation. This study was conducted with the aim of describing and analyzing the measurement of biological assets using the fair value approach and the cost approach at Brawijaya Farm with reference to IAS 41 or the standard applicable in Indonesia, namely PSAK 69 on agriculture with the concept of accretion. Accretion occurs when there is an increase in value caused by the process of growth and development of biological assets. In the accretion concept, revenue will be recognized along with the growth of biological assets. This study uses descriptive qualitative research methods, because this research is to describe and describe an event as it is. Descriptive qualitative research is research that aims to understand a phenomenon about what is being experienced by research subjects such as behavior, perception, action, and motivation, by means of descriptions of information data in the form of words and sentences, in a special natural context with using various scientific methods. The results of this study indicate that Brawijaya Farm has not recorded according to Financial Accounting Standards but in practice in the field there is some conformity with accounting standards that regulate agricultural business such as IAS 41 or PSAK 69 for example on pricing biological assets. according to its fair value. Regarding the accretion concept, Brawijaya Farm has capitalized all costs into its biological assets, this is in accordance with the accretion concept where costs incurred in connection with biological assets are capitalized into the value of biological assets.